Research on High School Students' and Teachers' Mental Health Literacy Levels in Istanbul, Turkey. (30th September 2020) - Karabey, S; Arslan, S
Abstract: Background: Mental health literacy (MHL) is critical to reduce health inequality and for raising awareness and early recognition of mental illnesses. This study among students and teachers in Istanbul, Turkey, aimed to (1) determine the knowledge levels towards mental illnesses, (2) identify barriers to help-seeking behaviors and (3) assess stigmatizing attitudes towards mental illnesses. Methodology: A cross-sectional, descriptive study design was used, and 810 high school students and 241 teachers were included in our study between Mar-Jul 2019. Data was collected through the Mental Health Literacy Questionnaire and the Beliefs towards Mental Illness Scale. Results: Students' recognition percentages of depression, schizophrenia and social phobia vignettes were found to be 27.5%, 47.7% and 6.2%, respectively. Teachers' were found to be 46.5%, 42.7% and 26.1%, respectively. A statistically significant relationship was found between students' correct recognition of vignettes and gender, age group, mother education levels, and father education levels (p < 0, 005). Female sex, older age, and having a parent with higher level of education were more likely to correct identify the vignettes. Among teachers, a significant relationship was found between correct recognition of vignettes and gender (p < 0, 005). Females were more likely to correct identify the vignettes. Regarding the BMI subscales, students' average score was 21, 6±9, 8 for "poor social and interpersonal skills and incurability", 19, 9±6, 9 for "dangerousness", 1, 5±2, 3 for "shame" and 42, 9±16, 2 for total scale and the teachers' average scores were 23, 6±10, 1, 21, 3±6, 6, 1, 2±1, 7 and 46, 2±16, 6 in the same order. Conclusions: The findings show that efforts are needed among both pupils and teachers in order to encourage help seeking behavior and to increase the belief that the solution of mental health problems is possible. Strengthening accessible mental health services and reducing stigma towards mental illnesses are also crucial.